Experimental Study on the Anisotropy and Non-coaxiality of Frozen Standard Sand under Different Principal Stress Directions - Dun Chen; Guoyu Li; Xiaodong Zhao; Wei Ma; Zhiwei Zhou; Yanhu Mu; Zejin Lai; Tuo Chen (Geofluids)
Owing to the limitations of the apparatus, the influence of its principal stress direction on the anisotropic behavior and non-coaxiality of frozen soil has not been fully considered in previous studies. At a temperature of -10°C, a series of hollow cylinder tests for frozen standard sand (FSS) was conducted under different directional angles of major principal stress and mean principal stresses in this study. The experimental results indicate that the stress-strain-strength anisotropy and non-coaxiality of the FSS are highly dependent on the principal stress direction. The stress components of the FSS vary linearly with increasing shear stress at different directional angles of the major principal stress and mean principal stresses. With a linear increase in shear stress, the strain components of the FSS exhibited a nonlinear increasing trend. The FSS strength gradually decreased as the directional angle of the major principal stress and the mean principal stresses in the test range increased. Under the different principal stress directions, the non-coaxiality of the FSS, non-coincidence of the direction of the principal strain increment and the principal stress direction, were observed. The directions of the principal strain increment and principal stress gradually tended to be coaxial as shear stress increased. Although the non-coaxial angle of the FSS increased gradually with an increase in the directional angles of the major principal stress, it did not change with the change in the mean principal stress. The non-coaxial angle of the FSS was observed to be as large as 35° in the early stage of shearing under different mean principal stresses.